Sexual assault and sexual harassment in the U.S. military. - Morral, Andrew R.; Gore, Kristie L.; Schell, Terry L., 1967- (Research report (Rand Corporation) ;, 2016)
"In early 2014, the Department of Defense Sexual Assault Prevention and Response Office asked the RAND National Defense Research Institute to conduct an independent assessment of the rates of sexual assault, sexual harassment, and gender discrimination in the military -- an assessment last conducted in 2012 by the Department of Defense using the Workplace and Gender Relations Survey of Active Duty Members. The resulting RAND Military Workplace Study invited close to 560,000 U.S. service members to participate in a survey fielded in August and September of 2014. This volume presents the results of methodological investigations into sources of potential bias in the survey estimates for active- and reserve-component service members. It includes evaluations of follow-up studies of survey nonrespondents and the efficacy of sampling weights to correct nonresponse bias, an assessment of total survey error using an administrative records benchmark, estimates of potential under- and overcounting of service members exposed to sexual assault, comparisons of events identified by prior survey forms and the RAND forms, analysis of survey non-consent and breakoff, and evaluation of service member tolerance of the RAND forms. In the final chapter, the report draws conclusions and recommendations for future administrations of sexual assault and harassment surveys in the military"--Publisher's description.